2021
DOI: 10.1111/luts.12407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on lower urinary tract symptoms in patients with benign prostatic hyperplasia and predictors of urine retention in such patients

Abstract: Objectives We assess the effect of coronavirus disease 2019 (COVID‐19) on lower urinary tract symptoms (LUTS) of patients with benign prostatic hyperplasia (BPH). Moreover, we delineate risk factors for urine retention in such patients. Methods All COVID‐19 infected males were expeditiously evaluated. All enrolled patients were assessed using the International Prostate Symptom Score (IPSS), uroflowmetry, and pelvi‐abdominal ultrasonography for prostate volume and postvoiding residual urine (PVR) estimation. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“… 9 In this context, some studies in the adult literature report COVID‐19 may cause exacerbation of LUTS in patients with benign prostatic hyperplasia and may even be a predictor of urinary retention. 11 Even an occult meningeal reaction has been reported in an elderly patient, independent of COVID‐19, on the basis of urinary retention of undetermined etiology. 12 This shows that every possibility should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In this context, some studies in the adult literature report COVID‐19 may cause exacerbation of LUTS in patients with benign prostatic hyperplasia and may even be a predictor of urinary retention. 11 Even an occult meningeal reaction has been reported in an elderly patient, independent of COVID‐19, on the basis of urinary retention of undetermined etiology. 12 This shows that every possibility should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been noted that urinary retention may be originating from febrile systemic infections (eg, viral, enteric, and nonurogenital), albeit to a lesser extent 9 . In this context, some studies in the adult literature report COVID‐19 may cause exacerbation of LUTS in patients with benign prostatic hyperplasia and may even be a predictor of urinary retention 11 . Even an occult meningeal reaction has been reported in an elderly patient, independent of COVID‐19, on the basis of urinary retention of undetermined etiology 12 .…”
Section: Discussionmentioning
confidence: 99%
“… 48 Nabeeh et al indicated that, among men receiving COVID-19 treatment, 13 patients experienced acute urinary retention and required urethral catheters and 15 patients underwent transurethral resection of the prostate. 44 They also noticed that patients requiring intensive care with the complaint of severe respiratory distress had higher IPSSs than patients hospitalized in the ward. 44 Similarly, a different study revealed that COVID-19 patients with high IPSSs had a significantly higher need for intensive care and mortality rates than those with low IPSSs.…”
Section: Benign Prostatic Hyperplasia (Bph) and Lower Urinary Tract S...mentioning
confidence: 99%
“…In three patients with the diagnosis of microhematuria, SARS-CoV-2 caused viral cystitis exacerbating local inflammation in urothelial cells which eventually led to irritative LUTS. [43] , [44] Nabeeh et al showed that immunosuppression is associated with increased LUTS, severe pyuria and urinary tract infections. 44 A previous study found increased urinary frequency, as one of the symptoms of COVID-19, in seven out of 57 COVID-19 patients.…”
Section: Benign Prostatic Hyperplasia (Bph) and Lower Urinary Tract S...mentioning
confidence: 99%
See 1 more Smart Citation